Monday
March 27, 2017

Post a New Question

Posted by on .

use the double angle formula to rewrite.

6cos^2-3

and


(cosx +sinx)(cosx-sinx)

  • Trigonometry - ,

    cos ( 2 x ) = 2 cos ^ 2 ( x ) - 1


    6 cos ^ 2 ( x ) - 3 =

    3 [ 2 cos ^ 2 ( x ) - 1 ] =

    3 sin ( 2 x )

  • Trigonometry - ,

    second one:

    (cosx +sinx)(cosx-sinx)
    =(cosx +sinx)(cosx-sinx) * (cosx + sinx)/(cosx + sinx)
    = (cos^2 x + 2sinxcosx + sin^2 x)/(cos^2 x - sin^2 x)
    = (1 + sin 2x)/cos 2x
    or
    1/cos 2x + sin 2x/cos 2x
    = sec 2x + tan 2x

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question